PENGARUH SEMANGAT KERJA, PELATIHAN KERJA, DAN PENEMPATAN PEGAWAI TERHADAP KEPUASAN KERJA ASN BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) SITUBONDO - Karnadi Karnadi; Riska Ayu Pramesthi (Relawan Jurnal Indonesia, 2020)
This study aims (1) to determine the effect of the variable work enthusiasm, job training and employee placement partially affect the variable job satisfaction of ASN BKPSDM Situbondo (2) to determine the effect of the variable work enthusiasm, job training and employee placement simultaneously affect the variable job satisfaction ASN BKPSDM Situbondo (3) to find out whether the variables of work spirit, job training and employee placement have a simultaneous effect on the variable job satisfaction of ASN BKPSDM Situbondo. The method used in this study is a quantitative method. The result of this research is multiple linear regression equation Y =. Y = 8.397E-17+ 0.174X1 +0, 852X2 - 0, 019X3 + e. Morale is 6.490, job training has a significant effect with a value of 31.264, amounted to 2.034, employee placement has a significant positive effect with a value of -1.230, amounted to 2.034, partially employee placement has no significant effect with a value of -1.230 of 2.034. Simultaneously or the F test shows the value of Fcount 1537.671 > Ftable 2.89. The most dominant variable in this study is job training with a tcount of 31.264.